N3-butyl imidazolium-based anion exchange membranes blended with Poly (vinyl alcohol)for alkaline water electrolysis - Park, H. J.; Lee, S. Y.; Lee, T. K.; Kim, H. J.; Lee, Y. M.
Blended membranes composed of a series of N3-butyl-substituted imidazolium-based poly(1-vinyl-3-imidazole-co-styrene)(PIS), prepared via radical polymerization, and poly(vinyl alcohol)(PVA), were used as anion exchange membranes (AEM)for alkaline water electrolysis (AWE). PISPVAx blend membranes (where x denotes the ratio of imidazolium group and styrene in PIS being 4:6, 3:7, and 2:8)were doped with 6 M KOH solution to prepare OH? conductive AEMs and their thermal and mechanical properties, chemical stabilities, and hydration properties were analyzed. With increasing imidazolium (PIS)ratio, the PISPVAx blend membranes show phase separation between the hydrophobic and hydrophilic polymer chains, and thus, feature well-connected hydrophilic channels. The highest ionic conductivity of 89.7 mS cm? was observed for the PISPVA46 membrane when using with 0.5 M KOH solution at 60 °C. The outstanding electrochemical performance of the PISPVA46 membrane, compared with those of PISPVA37 and PISPVA28, was reflected in a current density of 547.7 mA cm? at a cell voltage of 2.0 V. The higher imidazole ratio in the blend membrane produced an increase in the elongation at break and hydration property, such as water uptake and IEC, that obviously enhances the ion conducting capability of the resulting AEMs. Additionally, the KOH molecules were introduced into the membrane through PVA, resulting in high KOH uptake. Therefore, the PISPVAx blend membranes are useful candidates for anion exchange membrane water electrolysis (AEMWE)systems.
Keywords: WATER ELECTROLYSIS; ANION EXCHANGE MEMBRANE (AEM); POLY(1-BUTYL-3-VINYLIMIDAZOLE-CO-STYRENE); POLY(VINYL ALCOHOL); IMIDAZOLIUM IONIC LIQUID